Large-scale wet-spinning of highly electroconductive MXene fibers - Wonsik Eom (Nature Portfolio, 2020)
Large-scale production of fibers from two dimensional materials opens a pathway to promising applications. Here the authors report meter-long MXene fibers with high electrical conductivity that are fabricated via continuous wet spinning and demonstrated in electrical wires.